Trace metal data from water samples collected during RRS James Clark Ross cruise JR271 in the Nordic Seas - Yaqing Ruan; Tim Steffens; Stephan Krisch; Eric Pieter Achterberg (PANGAEA, 2025)
The file contains dissolved trace metal and total dissolvable trave metal concentrations (V, Mn, Fe, Co, Ni, Cu, Zn, Cd and Pb) of surface water samples (from towed fish) and station depth profiles (from Titanium CTD rosette equipped with Ocean Test Equipment (OTE) bottles at stations 1–6, 9, 10, 16, 38, 42, and 44, or OTE bottles mounted on plastic-coated wire at stations 11, 12, 14, 18, 19, 21, 26, 28, 30, 32, 34, 36, and 40) in the Nordic Seas during RRS James Clark Ross cruise JR271 between 1 June and 2 July 2012. Trace metal concentrations were measured by ICP-MS after preconcentration exactly as per Rapp et al., (2017) (doi.org/10.1016/j.aca.2017.05.008). Uncertainty is calculated as one standard deviation (1σ, STD) to replicate measurements via ICP-MS. ND = no data. Use of quality flags (QCFlag) according to GEOTRACES policy (https://www.geotraces.org/geotraces-quality-flag-policy/). Information on the analytical procedure including Certified Reference Material and limits of detection can be found in the related published manuscripts or can be obtained from the authors upon request.